2009
DOI: 10.1038/ni.1718
|View full text |Cite
|
Sign up to set email alerts
|

Memory T cells in nonlymphoid tissue that provide enhanced local immunity during infection with herpes simplex virus

Abstract: Effective immunity is dependent on long-surviving memory T cells. Various memory subsets make distinct contributions to immune protection, especially in peripheral infection. It has been suggested that T cells in nonlymphoid tissues are important during local infection, although their relationship with populations in the circulation remains poorly defined. Here we describe a unique memory T cell subset present after acute infection with herpes simplex virus that remained resident in the skin and in latently in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
1,190
5
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 991 publications
(1,234 citation statements)
references
References 46 publications
34
1,190
5
5
Order By: Relevance
“…This local proliferation also explains the observations of lymphoid follicles observed in the stomach after long-term infection [47]. Recently, local recall memory responses in peripheral non-lymphoid tissues at least for CD8 1 T cells have been shown to act to control herpes simplex infection [48]. Our data would indicate a similar local recall response for CD4 1 T cells occurs in the stomach for H. pylori infection.…”
Section: Discussionsupporting
confidence: 85%
“…This local proliferation also explains the observations of lymphoid follicles observed in the stomach after long-term infection [47]. Recently, local recall memory responses in peripheral non-lymphoid tissues at least for CD8 1 T cells have been shown to act to control herpes simplex infection [48]. Our data would indicate a similar local recall response for CD4 1 T cells occurs in the stomach for H. pylori infection.…”
Section: Discussionsupporting
confidence: 85%
“…Recognizing that resident T cells can be identified by the presence of CD69 and CD103 (Gebhardt et al., 2009), in preliminary studies we determined CD69 and CD103 expressions (Figure S1b). CD69 was widely expressed on FRT T cells, while CD103 expression was more restricted.…”
Section: Resultsmentioning
confidence: 99%
“…Following antigen recognition, naïve T cells differentiate into effector and memory T cells. Tissue‐resident memory T cells (TRMs) are a subset of memory cells that remain in tissues and do not recirculate (Gebhardt et al., 2009; Mueller & Mackay, 2016). CD8 + TRMs can be identified by the expression of CD69 and CD103, the αE portion of the αEβ7 integrin that allows interactions with E‐cadherin expressed on epithelial cells (Rosato, Beura & Masopust, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from murine experiments and studies of T cell depletion in human skin T cell malignancies (leukemic CTCL and mycosis fungoides) suggest that central memory T cells from skin regularly recirculate, whereas this is not the case for skin effector memory cells (28,29). However, the possibility of migration to the draining LN (but not recirculation to other tissues) following Ag stimulation was not excluded, especially for CD4 + T cells, and indeed, it is reported that some patients with malignant disease of effector memory T cells (mycosis fungoides) can develop LN involvement (28).…”
Section: Discussionmentioning
confidence: 99%